Aspek Hukum Pembentukan Holding Pangan BUMN - Alismata Samodra, Dorothea; Taruno Muryanto, Yudho (Res Publica: Jurnal Hukum Kebijakan Publik, 2022)
This article aims to discuss the legal aspects of the formation of food holding of State-Owned Enterprises (SOEs) in Indonesia. This legal research is a normative legal research. The research approach used is a qualitative approach. The data used are primary and secondary data. The data collection technique used is literature study and analyzed prescriptively to explain legal concepts relevant to the legal issues discussed. From the studies that have been carried out, the results obtained are the legal aspects of the formation of BUMN food holding carried out based on the provisions of PP Number 72 of 2016 concerning Amendments to Government Regulation Number 44 of 2005 concerning Procedures for Participation and Administration of State Capital in State-Owned Enterprises and Limited Liability Companies. This provision is used as the basis for transferring the capital of subsidiaries from the Ministry of Finance to / into the capital of PT RNI (Persero) which then acts as the owner of capital in the subsidiary.